1997
DOI: 10.1177/002215549704500603
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of c-fos In Vitro by All Anterior Pituitary Cell Types During the Estrous Cycle: Enhanced Expression by Luteinizing Hormone but Not by Follicle-stimulating Hormone Cells

Abstract: C-fos expression appears in some activated cell types. Because of dynamic changes in gonadotropes during the estrous cycle, this study was initiated to determine if fos might be expressed in gonadotropes before any period of activation. We detected c-fos and pituitary antigens in dissociated anterior pituitary cells by dual-labeling immunocytochemistry. The highest percentage of cells with fos protein were found in proestrous rat populations. In diestrous and proestrous populations, dual labeling showed that 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…The present studies and recent publications (Cesnjaj et al 1994;Armstrong and Childs 1997b) provide proof that normal gonadotropes express fos. In our recent study, the highest expression of fos by pituitary gonadotropes (metestrus) did not coincide with the highest expression of GnRH receptors (Lloyd and Childs 1988) (proestrus).…”
Section: Effects Of Gnrh On Fos Proteinssupporting
confidence: 85%
See 2 more Smart Citations
“…The present studies and recent publications (Cesnjaj et al 1994;Armstrong and Childs 1997b) provide proof that normal gonadotropes express fos. In our recent study, the highest expression of fos by pituitary gonadotropes (metestrus) did not coincide with the highest expression of GnRH receptors (Lloyd and Childs 1988) (proestrus).…”
Section: Effects Of Gnrh On Fos Proteinssupporting
confidence: 85%
“…However, the dual labeling evidence indicated that most of the fos-bearing cells in this population are not gonadotropes (Armstrong and Childs 1997b). This initially raised a question about fos as a third messenger in the activation of the gonadotrope during proestrus and led to subsequent studies designed to learn if GnRH can stimulate fos expression by gonadotropes from proestrous rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative cellular specificity of Egr1 transcription is interesting because it is distinct from other inducible transcription factors such as c-Fos, for example, that is expressed equally in all types of pituitary hormone-producing cells in female rats (Armstrong & Childs 1997). The specific sequences that direct Egr1 expression to pituitary sub-populations are interesting for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of c-fos to the regulation of the ovulatory cycle is suggested by the variation of c-fos expression between the stages of the cycle [11]. However, information on the manner in which c-fos is regulated by peptides, although vital to understanding longer-term gonadotrope control, is limited.…”
Section: Introductionmentioning
confidence: 99%